Isolating Fe Atoms in N‐Doped Carbon Hollow Nanorods through a ZIF‐Phase‐Transition Strategy for Efficient Oxygen Reduction - Ma, Fei‐Xiang; Liu, Zheng‐Qi; Zhang, Guobin; Xiong, Yu‐Xuan; Zhang, Meng‐Tian; Zheng, Lirong; Zhen, Liang; Xu, Cheng‐Yan (Small (Weinheim an der Bergstrasse, Germany), 2022)
Transition metal–nitrogen–carbon (TM–N–C) catalysts have been intensely investigated to tackle the sluggish oxygen reduction reactions (ORRs), but insufficient accessibility of the active sites limits their performance. Here, by using solid ZIF‐L nanorods as self‐sacrifice templates, a ZIF‐phase‐transition strategy is developed to fabricate ZIF‐8 hollow nanorods with open cavities, which can be subsequently converted to atomically dispersed Fe‐N‐C hollow nanorods (denoted as Fe1–N–C HNRs) through rational carbonization and following fixation of iron atoms. The microstructure observation and X‐ray absorption fine structure analysis confirm abundant Fe–N4 active sites are evenly distributed in the carbon skeleton. Thanks to the highly accessible Fe‐N4 active sites provided by the highly porous and open carbon hollow architecture, the Fe1‐N‐C HNRs exhibit superior ORR activity and stability in alkaline and acidic electrolytes with very positive half‐wave potentials of 0.91 and 0.8 V versus RHE, respectively, both of which surpass those of commercial Pt/C. Remarkably, the dynamic current density (JK) of Fe1‐N‐C HNRs at 0.85 V versus RHE in alkaline media delivers a record value of 148 mA cm−2, 21 times higher than that of Pt/C. The assembled Zn‐air battery using Fe1–N–C HNRs as cathode catalyst exhibits a high peak power density of 208 mW cm−2. By using solid ZIF‐L nanorods as self‐sacrifice templates, a unique ZIF‐phase‐transition strategy is developed to fabricate atomically dispersed Fe–N–C hollow nanorods (Fe1–N–C HNRs) with highly open architecture and abundant exposed Fe–N4 active sites, which can be utilized as efficient oxygen reduction reaction electrocatalysts in both alkaline and acid conditions.